Excellence Recognised: Academic Award 2017 / Mohammad Safwan Suimi - Suimi, Mohammad Safwan (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
This ceremony was organized by the Institute of Leadership and Development, Academic Affairs Division of UiTM Perak Branch at Dewan Seri Iskandar and the ceremony was launched by the honorable Datin Paduka Ir. Dr. Siti Hamisah Tapsir, the General Manager of Higher Education from Ministry of Higher Ed-ucation. UiTM Perak Academic Awards that was introduced in 2016, is aimed to recognise academicians who attain excellent accom-plishments in their respective fields.